Somatic Embryogenesis in Cashew (Anacardium Occidentale L.) - AGBIDINOUKOUN, ARNAUD (Shubhpriya Gupta and Preeti Chaturvedi, 2022)
Abstract Somaticembryogenesishasseenmanyadvances.However,manyaspects are not fully understood especially on cashew (Anacardium occidentale) despite several studies conducted for the technique improvement. Regenerate in vitro viable embryos through asexual cells (haploid or diploid) is the target of somatic embryogenesis. This process leads to the production of bipolar structures with root/shoot axis well deﬁned. The in vitro culture of cashew is brought out with emphasis on the critical factors that inﬂuence the explants response and plantlet regeneration. The recalcitrant nature of cashew has been attributed to abnormal development observed in the calli derived from its explants in some cases and to the limited success recorded up to here in tissue culture of the plant. This review highlights advances, challenges, and future prospects in somatic embryogenesis research of cashew.